Post Covid-19 world order: An Analytical study - Ahmad Shah, Mubashir; Altaf Dar, Mohmad (International Journal of Psychosocial Rehabilitation, 2020)
The world is going through its most challenging crisis since World War II. The COVID-19 epidemic is one of the most challenging disasters that humanity has faced in the twenty-first century, with no end in sight. Despite the fact that governments are busy treating corona-affected people and attempting to find a means to end this calamity, the worldwide impacts of this present pandemic are still being felt. The impacts of this pandemic are very significant for the existing political and economic leadership. In all aspects, COVID-19 will be a step towards the new world order. The present paper tries to understand how the current pandemic has affected the contemporary world order and what are the key factors that will determine the new world order post-COVID-19. Further, it also looks at the uncertainties that lie ahead and how India can contribute in shaping the new world order. To achieve these objectives, the analysis will be conducted following the qualitative methods, specifically analytical, descriptive, and evaluative methods.